O Inimigo em Pedaços: um ensaio da discussão bibliográfica acerca dos Tupi-Guarani - Marchioro, Márcio (Revista Vernáculo, 2002)
O Inimigo em Pedaços: um ensaio da discussão bibliográfica acerca dos Tupi-Guarani